APLIKASI SENDAI FRAMEWORK FOR DISASTER RISK REDUCTION DALAM TANGGAP DARURAT BENCANA [APPLICATION OF SENDAI FRAMEWORK FOR DISASTER RISK REDUCTION IN EMERGENCY DISASTER RESPONSE] - Saputra, Ilham; Rahmat, Hayatul Khairul (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2024)
This study aims to determine: the definition of emergency response in disaster, Sendai Framework for Disaster Risk Reduction as an International Agreement, Implementation of Sendai Framework at National and Local Levels, Role of stakeholders in the implementation of Sendai Framework, and Contribution of Sendai Framework to Sustainable Development. This research uses the literature study method. The findings of this study are that performance evaluation has forms such as aiming to find out how to implement the Sendai Framework in disaster emergency response.  In addition, the goal of the Sendai Framework for Disaster Risk Reduction in the context of disaster emergency response is to reduce the risks and impacts of disasters through a more integrated and comprehensive approach. In this process, it emphasizes the importance of disaster risk management as a top priority, not just a response to disasters after they occur.